Spatiotemporal organization of Aurora-B by APC/CCdh1 after mitosis coordinates cell spreading through FHOD1 - Floyd, Suzanne; Whiffin, Nicola; Gavilan, Maria P.; Kutscheidt, Stefan; De Luca, Maria; Marcozzi, Chiara; Min, Mingwei; Watkins, Johnathan; Chung, Kathryn; Fackler, Oliver Till; Lindon, Catherine (Journal of cell science, 2013)
Spatiotemporal regulation of mitotic kinase activity underlies the extensive rearrangement of cellular components required for cell division. One highly dynamic mitotic kinase is Aurora-B (AurB), which has multiple roles defined by the changing localisation of the chromosome passenger complex (CPC) as cells progress through mitosis, including regulation of cytokinesis and abscission. Like other mitotic kinases, AurB is a target of the anaphase-promoting complex (APC/C) ubiquitin ligase during mitotic exit, but it is not known if APC/C-mediated destruction plays any specific role in controlling AurB activity. We have examined the contribution of the Cdh1 coactivator-associated APC/CCdh1 to the organization of AurB activity as cells exit mitosis and re-enter interphase. We report that APC/CCdh1-dependent proteolysis restricts a cell-cortex-associated pool of active AurB in space and time. In early G1 phase this pool of AurB is found at protrusions associated with cell spreading. AurB retention at the cortex depends on a formin, FHOD1, critically required to organize the cytoskeleton after division. We identify AurB phosphorylation sites in FHOD1 and show that phosphomutant FHOD1 is impaired in post-mitotic assembly of oriented actin cables. We propose that Cdh1 contributes to spatiotemporal organization of AurB activity and that organization of FHOD1 activity by AurB contributes to daughter cell spreading after mitosis.